Murilo Rubião: enlaces eróticos, fantásticos e absurdos - Silva Júnior, Romão Inácio da (2006)
The present research intends to propose a reading in a new dimension of the fantastic (weird) literature and, especially, of its Brazilian more representative author, Murilo Rubião. At the beginning with concepts and associations with the erotic, starting from the myth of Eros and Psique and developing relations with Georges Bataille's theory on the theme. Afterwards, other associations are made, now with relation to the own fantastic literature. With the essence of this literature, examples of the traditional close to the contemporary. A last, association is made with the absurd literature. The contemporary man as being object and its configuration represented in the field of the dreams and its possibilities. At the end of the work, a "post scriptum" suggests a more imersive reading of tales in the entire that appeared broken into fragments along the research